Microencapsulation as a Route for Obtaining Encapsulated Flavors and Fragrances - Agnieszka Kłosowska; Agata Wawrzyńczak; Agnieszka Feliczak-Guzik (Cosmetics, 2023)
Microencapsulation methods for active substances, such as fragrance compounds and aromas, have long been of interest to researchers. Fragrance compositions and aromas are added to cosmetics, household, and food products. This is often because the choice of a particular product is dictated by its fragrance. Fragrance compositions and aromas are, therefore, a very important part of the composition of these items. During production, when a fragrance composition or aroma is introduced into a system, unfavorable conditions often exist. High temperatures and strong mixing have a detrimental effect on some fragrance compounds. The environments of selected products, such as high- or low-pH surfactants, all affect the fragrance, often destructively. The simple storage of fragrances where they are exposed to light, oxygen, or heat also has an adverse effect. The solution to most of these problems may be the encapsulation process, namely surrounding small fragrance droplets with an inert coating that protects them from the external environment, whether during storage, transport or application, until they are in the right conditions to release the fragrance. The aim of this article was to present the possible, available and most commonly used methods for obtaining encapsulated fragrances and aromas, which can then be used in various industries. In addition, the advantages and disadvantages of each method were pointed out, so that the selection of the appropriate technology for the production of encapsulated fragrances and aromas will be simpler.